2021
DOI: 10.18548/aspe/0009.20
|View full text |Cite
|
Sign up to set email alerts
|

Dry Cow Antimicrobials Use to Control Mastitis in Northern Algeria

Abstract: The control of mastitis is a crucial step in the preparation of the next lactation in dairy cows. In order to assess the practices and attitudes surrounding the use of antimicrobials at dry-off, a survey was conducted among veterinary practitioners in fifteen provinces of Northern Algeria. The results revealed that 45.95% of the farms followed by the respondents were rather small in size comprising about ten cows per farm and that a large majority of the farmers practised gradual drying off (72.97%) without ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The dry-off method used on the farms was the progressive method, which is similar to a study conducted in northern Algeria (Hamlaoui et al 2021). The average dry-off period was 62.1 days, which differs from the situation on 83% of farms in the United Kingdom, where the average length of the dry period was 56 days and farmers stop milking abruptly, regardless of the milk production level at dry-off (Fujiwara et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The dry-off method used on the farms was the progressive method, which is similar to a study conducted in northern Algeria (Hamlaoui et al 2021). The average dry-off period was 62.1 days, which differs from the situation on 83% of farms in the United Kingdom, where the average length of the dry period was 56 days and farmers stop milking abruptly, regardless of the milk production level at dry-off (Fujiwara et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Not separating animals in the drying-off period that might still be under antibiotic treatment from other lactating cows is another point of particular attention to be taken into account, which could explain the presence of antibiotic residues in milk. Indeed, a study conducted in northern Algeria (Hamlaoui et al, 2021) revealed that only 2.7% of farmers always separated dry cows from lactating ones.…”
Section: Antibiotic Residue Detectionmentioning
confidence: 99%
“…There is also a tendency for some farmers to direct the milk of cows undergoing antibiotic treatment to calf feed, which is another critical point (Hamlaoui et al, 2021).…”
Section: Antibiotic Residue Detectionmentioning
confidence: 99%